Sistema crediticio y su incidencia en el desarrollo socio-económico de los clientes de Credife banco Pichincha cantón Ventanas, periodo 2011-2012, programa de capacitación. - Ron Campoverde, Jorge Luis (2013)
This research was conducted at Pichincha´s Bank Credife, because some of the problems identified: What affects the credit system in the socio-economic Credife customers Pichincha´s Bank Windows City? Among the problems encountered are: the process of Credife lending, the cost and time of credit financing and the amount of debt financing. Was intended to know how these variables are influencing the socio-economic development customers Credife, Windows City. For credit system is understood as the process of granting credit to be granted for a specified period and for a specific purpose. The objectives in the thesis research are: Evaluate the impact of Credife Credit System of Pichincha´s Bank, in the socio-economic development of the Windows City clients. Analyze the credit granting process Credife Pichincha´s Bank and its impact on the placement of Windows City on credits. To Determine the economic development agency clients Credife Windows and its relationship to the time and cost of credit financing. The development of these objectives allowed to reach the real solution of the problem. It showed the following hypothesis: The credit system of Pichincha´s Bank Credife positive impact on socio-economic development of the Windows City clients. Where the desire is to improve the productive apparatus of this county especially Credife portfolio of clients. The purpose of the thesis work was to determine the impact of the credit system in the socio-economic Credife customers Pichincha´s Bank Windows City. Credife Microenterprise Development aims to support the productive critical in this case Windows City and surrounding areas according to established requirements. This institution has a good number of customers at all levels of production, having many years in the market.............................................................